Toxicity of targeted anticancer drugs: a theoretical analysis of mechanisms and mitigation strategies - HICHEM Saadallah (. جامعة الوادي.Université d'EL-Oued., 2025)
Since targeted therapy offers greater precision and generally better tolerance than standard chemotherapy, it has emerged as a key tactic in contemporary cancer treatment. These treatments do not, however, come without side effects, and their toxicity varies according to a number of clinical and molecular parameters. This study uses a theoretical approach grounded in a systematic review of scientific literature to investigate the toxicity caused by targeted anticancer drugs and the ways in which those effects can be controlled or lessened. It draws attention to how different treatments can cause diverse side effects and stresses how crucial early discovery, individualized treatment, and cutting-edge technology are to reducing harm. In addition to offering a thorough analysis of toxicity in targeted cancer therapy, this study suggests methods for safer, more efficient implementations in oncological practice going forward.
Toxicology
Keywords: Targeted therapy; toxicity; personalized medicine; pharmacogenomics; drug delivery; HER2 inhibitors.